Report on Proceedings of the 12th Annual European CME Forum, University of Manchester, November 2019. Issue 1 (1st January 2020) - Murray, Ron; Macfarlane, Cara L
ABSTRACT: The 12th Annual European CME Forum (#12ECF) was held 6–8 November 2019 at the Barnes Wallis building in the University of Manchester, Manchester, UK. An international group of attendees participated in highly interactive learning sessions, ranging from workshops to panel discussions to oral presentations by poster authors. Breakout session themes addressed continuing medical education (CME) from the perspective of the learner ( micro -practice); collaborations, partnerships and interprofessional approaches ( meso -practice); and consideration of compliance and regulatory issues ( macro -practice). Topics covered included standards for accreditation, doctor-patient communication, a framework for CME educators' professional development, capacity building and a futurist viewpoint of continuing professional development (CPD) from a global perspective. The high level of engagement by learners set a solid foundation for further collaboration among stakeholders in European CME.